Mechanical Properties of Concrete Containing Reclaimed Asphalt Pavement (RAP) and Fly Ash as Replacement Materials - Nurul Ain Kamilia Abd Nasir; Ahmad Jeni, Mohd Luthfi; Kosnin, Hilmi; Osman, Mohamad Hairi (Progress in Engineering Application and Technology, 2022)
Nowadays, a lot of studies have been conducted on waste materials to replace coarse aggregates and cement in producing concrete. Use of the reclaimed asphalt pavement (RAP) and fly ash in the concrete will put on the concept of eco-friendly and also improve the strength of concrete while compared to common concrete that could damage the environment when used too much and costly in the future. In this study, RAP replaced up to 10% of the coarse aggregate, while fly ash replaced up to 9% of the cement in the concrete mixture. Tests were done to obtain data on the slump tests, density tests, water absorption tests, and compressive strength of concrete to determine the effectiveness of using reclaimed asphalt pavement and fly ash as replacement materials in the concrete mixtures. The performance of the RAP and fly ash replacement concrete was then compared to that of normal concrete. Furthermore, based on the results of the maturity of the concrete at 28 days, normal concrete and concrete with replacement materials of RAP and fly ash were stronger compared to only replacing RAP according to the prescribed percentage of replacement materials. Hence, the compressive strength was decreased when the percentage of replacement RAP and fly ash increased. Generally, the replacement percentage for fly ash is 10% to 20% acceptable, whereas RAP should not replace coarse aggregates more than 20%. In conclusion, the optimum content of RAP and fly ash are at 10% RAP and 3% fly ash of percentages where its compressive strength results in increases to 30.77 MPa after 28 days.